2021
DOI: 10.3390/jcm10092000
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Well and Recover Faster with Less Pain—A Narrative Review on Sleep in the Perioperative Period

Abstract: Sleep disturbance, pain, and having a surgical procedure of some kind are all very likely to occur during the average lifespan. Postoperative pain continues to be a prevalent problem and growing evidence supports the association between pain and sleep disturbances. The bidirectional nature of sleep and pain is widely acknowledged. A decline in sleep quality adds a risk for the onset of pain and also exacerbates existing pain. The risk factors for developing insomnia and experiencing severe pain after surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 117 publications
(132 reference statements)
3
17
0
Order By: Relevance
“…The results of this study showed that the overall quality of sleep, total sleep duration, and early awakening of the two groups of patients on the first night after surgery were significantly lower than those before surgery. These results concur studies showing prolonged sleep induction, shortened sleep duration, increased number of awakenings, and fragmented sleep after surgery [ 11 , 12 ]. Secretion of MT influences circadian rhythm and is closely related to the sleep rhythm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that the overall quality of sleep, total sleep duration, and early awakening of the two groups of patients on the first night after surgery were significantly lower than those before surgery. These results concur studies showing prolonged sleep induction, shortened sleep duration, increased number of awakenings, and fragmented sleep after surgery [ 11 , 12 ]. Secretion of MT influences circadian rhythm and is closely related to the sleep rhythm.…”
Section: Discussionsupporting
confidence: 92%
“…Functioning during the day 0 (0,0) 0 (0,0) 0 (0,1) 1 (0,1) bc Sleepiness during the day 0 (0,0) 0 (0,0) 0 (0,0) 0 (0,0) significantly lower than those before surgery. These results concur studies showing prolonged sleep induction, shortened sleep duration, increased number of awakenings, and fragmented sleep after surgery [11,12]. Secretion of MT influences circadian rhythm and is closely related to the sleep rhythm.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, administration of zolpidem one night before and on the first night after surgery improves sleep quality and fatigue. 3 , 26 …”
Section: Postoperative Sleep Disturbancementioning
confidence: 99%
“…Specifically, administration of zolpidem one night before and on the first night after surgery improves sleep quality and fatigue. 3,26 Sleep disturbances in AD patients are characterised by increased duration of awakenings, loss of SWS and REM sleep, and excessive daytime napping. AD patients spend a significant proportion of their day asleep, although this almost completely comprises stages 1 and 2 sleep, which barely compensates for night-time absences of SWS and REM sleep.…”
Section: Effects Of Psd On Postoperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation